ANALISIS FAKTOR - FAKTOR YANG BERPENGARUH TERHADAP CAPITAL ADEQUACY RATIO - METYRIA IMELDA HUTABARAT; EDY FIRMANSYAH; NIRWANA DEWI HARAHAP (LP2MTBM MAKARIOZ, 2019)
The purpose of this empirical research is to analyze whether the influence of Loan to Deposit Ratio (LDR), Net InterestMargin (NIM) and Return on Asset (ROA) toward Capital Adequacy Ratio (CAR). This study uses method probabilitysampling that met criteria of the research. The research period is taken for 4 years starting from 2015 to 2018. Datacollection in this research uses secondary data in the form of data collecting from the annual bank financial statementpublished on the Indonesia Stock Exchange and by each state-owned bank. The analytical method using multiple linearregression. The results show that LDR has a positive but not significantly effect toward CAR, NIM significant positive effecttoward CAR and ROA positive but not significantly effect toward CAR.